Peran Inovasi Produk, Content Marketing, dan Product Knowledge Dalam Mmepengaruhi Keputusan Pembelian Produk Kays Golden Nest Indonesia - Nurul Aisyah; Diana Puspitasari; Hertiana Ikasari; Guruh Taufan (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
Kays Golden Nest is a beverage brand that uses swallow’s nest as the main ingredient and is now increasingly well-known among Indonesian people, especially because of its image as a health drink. The rapid development in this industry reflects the great potential for the swallow’s nest business sector, even though market competition is getting tighter. The swallow’s saliva that has hardened and is then processed into a high-value drink is the source of this product. The purpose of this study was to assess the creative strategies used by Kays Golden Nest to develop its company. This study was conducted through a qualitative descriptive approach, where data were collected through a questionnaire. The result showed that methods such as product innovation, application of product knowledge, and content marketing can significantly help business planning and increase competitiveness. These three strategies are implemented by making updates in marketing techniques and innovations that are aimed at increasing consumer engagement and loyalty.